Molecular and Cellular Responses to Interleukin-4 Treatment in a Rat Model of Transient Ischemia. Issue 11 (November 2016) - Lively, Starlee; Hutchings, Sarah; Schlichter, Lyanne C.
Abstract : Within hours after stroke, potentially cytotoxic pro-inflammatory mediators are elevated within the brain; thus, one potential therapeutic strategy is to reduce them and skew the brain toward an anti-inflammatory state. Because interleukin-4 (IL-4) treatment induces an anti-inflammatory, "alternative-activation" state in microglia and macrophages in vitro, we tested the hypothesis that early supplementation of the brain with IL-4 can shift it toward an anti-inflammatory state and reduce damage after transient focal ischemia. Adult male rat striata were injected with endothelin-1, with or without co-injection of IL-4. Inflammation, glial responses and damage to neurons and white matter were quantified from 1 to 7 days later. At 1 day, IL-4 treatment increased striatal expression of several anti-inflammatory markers (ARG1, CCL22, CD163, PPARγ), increased phagocytic (Iba1-positive, CD68-positive) microglia/macrophages, and increased VEGF-A-positive infiltrating neutrophils in the infarcts. At 7 days, there was evidence of sustained, propagating responses. IL-4 increased CD206, CD200R1, IL-4Rα, STAT6, PPARγ, CD11b, and TLR2 expression and increased microglia/macrophages in the infarct and astrogliosis outside the infarct. Neurodegeneration and myelin damage were not reduced, however. The sustained immune and glial responses when resolution and repair processes have begun warrant further studies of IL-4 treatment regimens and long-term outcomes.